Indigenous brigades change the spatial patterns of wildfires, and the influence of climate on fire regimes - Oliveira, Maxwell R.; Ferreira, Bruno H. S.; Souza, Evaldo B.; Lopes, Aline A.; Bolzan, Fábio P.; Roque, Fábio O.; Pott, Arnildo; Pereira, Alexandre M. M.; Garcia, Letícia C.; Damasceno, Geraldo A.; Costa, Ademilson; Rocha, Mesaque; et al. (The Journal of applied ecology, 2022)
Indigenous people have been managing fire‐prone landscapes for millennia, especially in tropical savannas, thereby maintaining carbon stocks and pyrodiversity and ensuring food security. In some indigenous lands in Brazil, fire brigades are composed of indigenous people, integrating their traditional knowledge in Brazilian fire management policies; however, the effectiveness of their management is largely undocumented. Nevertheless, we need to know the effectiveness of indigenous fire brigades and their influence on fire patterns. Here, we evaluate an 18‐year historical series of fire patterns and burn scars, comparing periods with and without indigenous brigade activity, to describe the role of indigenous fire brigades in the Kadiwéu Indigenous Territory. In this Indigenous Territory, fire brigades composed of indigenous people have been instituted, trained and maintained by the National Center of Prevention and Combat of Wildfire (PREVFOGO/IBAMA) since 2009. These brigades are responsible for fire management throughout the Kadiwéu Indigenous Territory using controlled burning, prescribed burning and combating wildfires. We found that fire management by the indigenous brigades has reduced fire frequency by 80% in the areas with high fire frequency (over 70% of the analysed time). Management also reduced the size of the area burned by 53% and the influence of climate over the total area burned. According to our models, the area affected by fires is mainly influenced by annual rainfall in the absence of indigenous brigades; in contrast, climatic factors could not explain the variation in the burned area in the period without indigenous brigades. Synthesis and applications. The fire management realized by the indigenous brigades can modify the fire regime. These changes in the fire regime can include: changes in spatial patterns, the magnitude of fires and reduction in the influence of climate on fire regimes. Hence, the management carried out by the indigenous brigades can be considered an important tool for fire management. In addition to demonstrating the importance of programs that integrate traditional indigenous knowledge with fire management policies, such as the Integrated Fire Management (IFM), to construct effective management strategies. Resumo Os povos indígenas vêm gerindo paisagens propensas ao fogo há milênios, especialmente nas savanas tropicais, mantendo assim os estoques de carbono e a pirodiversidade e garantindo a segurança alimentar. Em algumas terras indígenas no Brasil, as brigadas de incêndio são compostas por indígenas, integrando seus conhecimentos tradicionais nas políticas de manejo de incêndios; no entanto, a eficácia da sua gestão é em grande parte não documentada. Deste modo, precisamos conhecer a eficácia das brigadas de incêndio indígenas e sua influência nos padrões de incêndio. Neste estudo, avaliamos uma série histórica de 18 anos de padrões de incêndio e cicatrizes de queimadas, comparando períodos com e sem atividade de brigada indígena, para descrever o papel das brigadas indígenas na Terra Indígena Kadiwéu. Neste Território Indígena, desde 2009, brigadas de incêndio compostas por indígenas são instituídas, treinadas e mantidas pelo Centro Nacional de Prevenção e Combate a Incêndios (PREVFOGO/IBAMA). Estas brigadas são responsáveis pelo manejo do fogo em todo o território Kadwéu, utilizando técnicas como a queima prescrita, queima controlada e o combate a incêndios. Constatamos que o manejo de incêndios realizado pelas brigadas indígenas reduziu a frequência de incêndios em 80% nas áreas com alta frequência de incêndios (mais de 70% do tempo analisado). O manejo também reduziu em 53% o tamanho da área anual queimada e a influência do clima sobre a área total queimada. De acordo com nossos modelos, a área afetada pelos incêndios é influenciada principalmente pelas chuvas anuais na ausência de brigadas indígenas; em contrapartida, os fatores climáticos não puderam explicar a variação da área queimada no período sem brigadas indígenas. Síntese e aplicações. O manejo do fogo realizado pelas brigadas indígenas pode modificar o regime de fogo. Essas alterações no regime de fogo podem incluir: mudanças nos padrões espaciais, na magnitude dos incêndios e redução na influência do clima sobre os regimes de fogo. Assim, o manejo realizado pelas brigadas indígenas pode ser considerado uma importante ferramenta para o manejo do fogo. Além disso, demonstra a importância de programas que integrem o conhecimento tradicional indígena com políticas de manejo do fogo, como o Manejo Integrado do Fogo (MFI), para a construção de estratégias de manejo eficazes. The fire management realized by the indigenous brigades can modify the fire regime. These changes in the fire regime can include: changes in spatial patterns, the magnitude of fires and reduction in the influence of climate on fire regimes. Hence, the management carried out by the indigenous brigades can be considered an important tool for fire management. In addition, demonstrates the importance of programs that integrate traditional indigenous knowledge with fire management policies, such as the Integrated Fire Management (IFM), to construct effective management strategies.